If it's not what You are looking for type in the equation solver your own equation and let us solve it.
1+8=13+6n
We move all terms to the left:
1+8-(13+6n)=0
We add all the numbers together, and all the variables
-(6n+13)+1+8=0
We add all the numbers together, and all the variables
-(6n+13)+9=0
We get rid of parentheses
-6n-13+9=0
We add all the numbers together, and all the variables
-6n-4=0
We move all terms containing n to the left, all other terms to the right
-6n=4
n=4/-6
n=-2/3
| 12-t=5 | | x+31=-4x+18 | | 1/8x-3/10=1/10+3/16x | | 3y^2+20y+32=0 | | 24+2y-5=11y-11-4y | | 24+2y=12+4y | | ((2x/5)-(3x/4))=3 | | −1/8(x–4)=–4 | | 3(3c-1)=7c+2 | | 12m-4m=16 | | -x+3(-2x+3)=-12 | | 1b+83=-3b-5 | | 2y+15=-11 | | 4(v-20)=-16 | | 12(n+11)(3n-4)=0 | | −18(x–4)=–4 | | 16-3k=7 | | 7q-5q=14 | | 4x-7+86=9x-4 | | 2x(-2+x+x^2)=0 | | 16-4q=-8 | | 5+6x-12=6x-12-4x | | 5(x-4)=22 | | 3/2x-5/3=1/2x-5 | | 2z-z=3z-1+z | | 4z+15=9z-20 | | -f/6+5=2 | | (12x^2+19x-21)/(4x-3)-(7x^2-175)/(x^2-25)=((3+x)5+(x+3))+(7+x^2))/(4) | | 5x+2+6x+4+12x-4=x | | 0.8x-1.2=x-0.2 | | 2x(4-3x)x=2 | | 9=3(5-2d |